The literary twentieth century. Synchronic cuts and diachronic projections (Colloquia Comparativa Litterarum, 2025)
Cleo Protokhristova. The Literary Twentieth Century. Synchronic Cuts and Diachronic Projections. Plovdiv, Paisii Hilendarski UniversityPress, 2020